EXPLORING THE INTEGRATION OF ARTIFICIAL INTELLIGENCE WITHIN STEM EDUCATION THROUGH THE TPACK FRAMEWORK: EDUCATORS’ PERSPECTIVES AND EXPERIENCES - Dr. Zahida Javed; Dr. Khaliq Hussain; Saba Lajventi; Asma Bibi (International Journal of Contemporary Issues in Social Sciences, 2024)
In this paper researchers explore the suggestions for integration of artificial intelligence (AI) in STEM education by examining educators’ views and experiences based on the Technological Pedagogical Content Knowledge (TPACK). While AI is becoming more prevalent in education, a model does not yet exist to define how it can be integrated effectively into STEM curricula. For example, educators are having trouble integrating AI tools with their existing pedagogical practices and technology. While the TPACK framework may enhance some of these difficulties, earlier research has seldom employed it to AI integration in STEM education. This study intends to address this gap by explaining the lived-experience of educators’ AI integration with reference from TPACK, challenges and best practices backfired as well outcomes due to such integration. This study could be important to drive these educations practices forward and shows how the teacher training can be improved in order for students to get better prepared for future job markets. The qualitative data will be collected by conducting semi-structured interviews of 15-20 STEM educators, using a purposive sampling to obtain an in-depth understanding of the challenges and supports required for effective AI integration into STEM education.